528 EVALUATING THE PRESCRIPTION OF OPIATES IN PATIENTS WITH NECK OF FEMUR FRACTURES IN OUT OF HOSPITAL AND EMERGENCY CARE SETTING. (14th June 2021) - Kanabar, S; Mistry, D; Naeem, H; Smith, R; Zahir, F; Kumar, A; Gurung, Y K; Chatterjee, A
Abstract: Introduction: Opiate based analgesia forms a key component of Hip Fracture management. If prescribed inappropriately, opiate based analgesia can lead to respiratory depression, nephrotoxicity, and delayed recovery. The aim of this project was to evaluate opiate prescription in NOF patients in both out of hospital (OOH) and Emergency Department (ED). Methods: 100 consecutive patients were identified from National Hip Fracture Database between January and August 2019. Medical records were reviewed in both care settings, reviewing dose of morphine in comparison to body weight and renal function. Outcomes measured include constipation, acute kidney injury, respiratory compromise, and mortality. Statistical tests (t-test and chi square) were used to discern significance. Following the first cycle of results, results were disseminated to paramedics and at local governance meetings. Teaching was undertaken to increase awareness of harms associated with inappropriate opiate prescribing. A second cycle evaluated 30 consecutive NOFs from July 2020. Results: In our study population, 74% were female and the average age was 84. The range of morphine doses given OOH ranged from 2-40 mg, in comparison to 2.5-20 mg in ED. 18% of patient suffered from Respiratory depression with 48 hours of their admission with a further 7% suffering from an acute kidney injury. After intervention, OOH morphine doses ranged between 5-10 mg, a reduction of 75% on maximum dose, with increased use of adjuvants as guided by the WHO pain ladder. No adverse outcomes were noted within 48 hours of admission. Conclusion: Patient safety should be high on the agenda whilst caring for frail patients with Hip Fractures and opiate prescription is one of the most critical in the patient's journey. Reducing harm by prescribing the optimal opiates helps to reduce mortality, morbidity, improve rehabilitation and patient flow within the NHS pathways. A guideline has been published to aid opiate prescription in elderly patients.